From Career Anxiety to Work Readiness: The Mediating Effect of Career Self-Efficacy - Dewi Kurniawati; Gunawan Baharuddin; Bayu Retno; Fytha Poetri Agayha; Annisa Helmaliana (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study addresses the limited evidence on the simultaneous relationships among career anxiety, career self-efficacy, and work readiness by testing an integrated mediation model based on Social Cognitive Career Theory (SCCT).Research Methodology: A quantitative cross-sectional survey was conducted involving 374 final-year undergraduate students from accredited Indonesian universities selected through purposive sampling. Data were collected using a structured online questionnaire and analyzed with Structural Equation Modeling–Partial Least Squares (SEM-PLS) in SmartPLS 4.0 including measurement model evaluation and bootstrapping for hypothesis testing.Results: Career anxiety did not significantly influence work readiness directly (? = 0.092, p = 0.056). However, career anxiety significantly affected career self-efficacy (? = 0.536, p < 0.001), while career self-efficacy positively influenced work readiness (? = 0.677, p < 0.001). Bootstrapping results further demonstrated that career self-efficacy fully mediated the relationship between career anxiety and work readiness.Conclusions: Career self-efficacy represents the primary psychological mechanism through which career anxiety influences students’ readiness for employment. Strengthening students’ career self-efficacy can reduce the adverse effects of career anxiety and improve their transition into the labor market.Limitations: This study is limited by its cross-sectional design, reliance on self-reported data, and focus on final-year university students in Indonesia.Contributions: This study extends Social Cognitive Career Theory by integrating career anxiety, career self-efficacy, and work readiness within a mediation framework, offering practical implications for enhancing graduate employability in higher education.